Impact of steroid dose and timing on efficacy of combination PD-1/CTLA-4 blockade - Nina B. Curkovic; Rebecca Irlmeier; Xue Bai; Can Cui; Fei Ye; Hannah R. Burnette; Aleigha R. Lawless; Juliane Andrade Czapla; Ryan Sullivan; Douglas B. Johnson (OncoImmunology)
With the increasing use of immune checkpoint inhibitors (ICIs) in combination regimens and in earlier stages of advanced melanoma, the effective management of immune-related adverse events (irAEs) is key to balancing immunotherapy efficacy and toxicity. Conflicting evidence exists on possible detrimental effects of immunosuppression with corticosteroids for irAEs on ICI effectiveness. We conducted a multicenter, retrospective cohort study of immunotherapy-naïve advanced melanoma patients undergoing treatment with ipilimumab and nivolumab and a small cohort treated with nivolumab/relatlimab. We utilized univariate tests to assess response, PFS, and OS based on presence of irAE, receipt of steroids for irAEs, peak dose, and time-to-steroid, as well as multivariable analysis for response, OS, and PFS in patients receiving steroids for irAEs. Among 226 total ipilimumab/nivolumab patients, those without irAEs had poorer PFS and OS compared to irAE groups regardless of steroid administration. In subgroup analysis of patients receiving steroids for an irAE, increased time-to-steroid was significantly associated with improved response (aOR, 1.026 p = 0.0005), PFS (aHR, 0.986 p = 0.001), and OS (aHR, 0.983 p = 0.0008). Higher peak steroid dose was significantly associated with poorer PFS (aHR, 1.002 p = 0.005), and OS (aHR, 1.002 p = 0.003). Use of additional immunosuppressants was associated with poorer OS (aHR, 1.941 p = 0.018). Cumulative dose was not significantly associated with outcomes. Among 42 additional patients treated with nivolumab/relatlimab, irAEs were significantly associated with improved PFS/OS, which appeared to be slightly mitigated by steroid administration; dosing relationships were limited by small numbers.